INFLATION OR EXCHANGE RATES? RETHINKING THE SOURCES OF TRADE VOLATILITY IN ASIA (Contemporary Journal of Social Science Review, 2025)
This study investigates the macroeconomic determinants of trade volatility in twelve Asian economies from the period 2011 to 2024 using panel estimation techniques, including fixed effects, random effects, and two-way fixed effects models. The analysis explores how exchange rate volatility, inflation, trade openness, and economic growth influence trade stability across the region. The results indicate that inflation is the primary driver of trade volatility, emphasizing the importance of price stability in maintaining consistent trade performance, while exchange rate volatility shows limited statistical significance. Trade openness exerts a stabilizing effect, particularly in East and Southeast Asia, reflecting the moderating influence of regional and global value chain integration. Regional sub-sample estimations further reveal that economic growth intensifies trade volatility in South Asia but mitigates it in Southeast Asia. Overall, the findings underscore that sustained price stability and deeper structural integration are crucial for strengthening trade resilience in Asia, whereas exchange rate management alone provides limited stability benefits.